Reconciling Intent with Action: Factors Associated with the Alignment between Transfer Intent and Coursework Completion Patterns among Two-Year College Students in STEM. (9th November 2020) - Chan, Hsun-Yu; Wang, Xueli
ABSTRACT: In this study, we explored the alignment between initial transfer intent and subsequent course-completion patterns among 1, 668 first-time STEM-aspiring students at two-year institutions. Using survey and transcript data, we conducted latent profile analysis and subsequent path analysis that revealed five distinct course-completion patterns: Trailing/Time-Out, Non-transfer-Focused, Transfer: STEM Concentrated, Transfer: Humanity/Social Science Con-centrated, and Transfer: Developmental Education Concentrated . Students' math and science self-efficacy, academic engagement, and transfer-oriented interactions moderated the alignment between initial transfer intent and later course completion patterns. Based on the findings, we discuss the importance of cultivating strong academic self-efficacy and building effective advising practices to help students actualize their transfer intent.